PENGARUH KOMUNIKASI, LINGKUNGAN KERJA, PENGEMBANGAN KARYAWAN DAN MOTIVASI TERHADAP SEMANGAT KERJA KARYAWAN - Pamungkur Pamungkur (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The success of an organization is intensely influenced by the work spirit of the officers in performing their tasks and responsibilities. The officers who possess skill, energy, and creativity are the prominent resources of an organization to attain their purposes, not to mention for the Palangka Raya branch of The State electricity Company (PLN). Thereupon the objectives of this research were (1) To ascertain the communication influences to the work spirit of the Palangka Raya branch of The State electricity Company (PLN) officers, (2) To ascertain the influences of the work environment to the officers’ work spirit of the Palangka Raya branch of The State electricity Company (PLN), (3) To ascertain the officer development influences on the work spirit of the officers’ of The State electricity Company (PLN) in the Palangka Raya branch, (4) To ascertain the influences of officer motivation on the work spirit of the Palangka Raya branch of The State electricity Company (PLN) officers, (5) To discover how the communication, work environment, officer development and motivation influence the work spirit of the The State electricity Company (PLN) officers in Palangka Raya branch. The research results which were based on the descriptive analysis, communication variable, work environment, officer development and motivation indicated that there are positive influences. The communication, work environment, officer development and motivation simultaneously and significantly influenced the work spirit of the Palangka Raya branch of The State electricity Company (PLN) officers up to 99%, and the 1% remained was influenced by another factor in which is not included in the research.